Lab in the Field: Measuring Preferences in the Wild - Uri Gneezy; Alex Imas (Center for Economic Studies and ifo Institute (CESifo), 2016)
In this chapter, we discuss the “lab-in-the-field” methodology, which combines elements of both lab and field experiments in using standardized, validated paradigms from the lab in targeting relevant populations in naturalistic settings. We begin by examining how the methodology has been used to test economic models with populations of theoretical interest. Next, we outline how lab-in-the-field studies can be used to complement traditional Randomized Control Trials in collecting covariates to test theoretical predictions and explore behavioral mechanisms. We proceed to discuss how the methodology can be utilized to compare behavior across cultures and contexts, and test for the external validity of results obtained in the lab. The chapter concludes with an overview of lessons on how to use the methodology effectively.
Keywords: C90; C91; C93; 330; experiments; methodology; field experiments